Medication Review for Hospitalized Pediatric Patient: Clinical Pharmacist Interventions - (:unkn) unknown (My University, 2022)
Objective: The aim of this study is to evaluate clinical pharmacist-led medication review service for hospitalized pediatric patients. Material and Methods: This cross-sectional study was carried out between November 2017-April 2018 in an education and research hospital in Istanbul. Clinical pharmacist-led medication review was conducted by using Pharmaceutical Care Network Europe (PCNE) Classification V8.02 in hospitalized pediatric at general pediatric service. Potential drug-related problems (DRPs) were identified and classified. These DRPs were presented the physicians and the percentage of accepted recommendations by the physician were recorded. Results: Among forty-three patients (21 male and 22 female), the median age of them was calculated as 6 (3-36) months. Of them, 25.58% had 16 DRPs. The most common DRPs were associated with potential drug-drug interactions (n= 9); and dose selection (n= 5), which represented 56.25% and 31.25% of drug-related problems, respectively. It was observed that 63% of these problems were occurred during selection of drugs (at prescription level) according to PCNE classification. Of the clinical pharmacist’s recommendations regarding these DRPs, 87.5% were accepted by the physician. Conclusion: To optimize rational drug use, numerous studies related with clinical pharmacist-led medication review by using PCNE classification were present in adult patients; however, there was no sufficient studies conducted in pediatric patients. Clinical pharmacists have an important role in the classification of DRPs and to provide rational drug use in pediatric patients.